Reduced Size Frequency Agile Microwave Circuits Using Ferroelectric Thin-Film Varactors - Lourandakis, Errikos; Schmidt, Matthias; Seitz, Stefan; Weigel, Robert (IEEE Transactions on Microwave Theory and Techniques, 2008)
A new concept for tunable and reduced size microwave circuits is presented based on barium-strontium-titanate (BST) varactors. The proposed design methodology relies on substitution of quarter-wavelength transmission line segments with their equivalent low-pass structures. The ferroelectric BST-varactors are used as tuning elements and allow for a frequency agile behavior and size reduction of the circuit. Candidates for this methodology are quarter-wavelength based circuits such as Wilkinson power dividers and branch-line couplers. Prototype boards for both topologies were implemented and characterized through scattering parameter measurements. For the implemented Wilkinson divider a tuning range from 1.7 to 2.1 GHz is achieved. The insertion loss in both output paths varies from 0.6 to 1.2 dB while maintaining a worst case amplitude- and phase difference of 0.5 dB and 9deg, respectively, for all operating cases. The isolation between the two output ports exceeded 25 dB over the whole tuning range. The implemented branch-line coupler exhibits a tuning range from 1.8 to 2.3 GHz with a maximum insertion loss of 2.7 dB while maintaining worst case amplitude- and phase difference of 0.4 dB and 90deg plusmn 5deg, respectively. Port matching and isolation levels of more than 15 dB are exhibited at all bias conditions.
elib2cris::1512001600,lourandakis2008d